CLINICAL RESEARCHTransplantation of bone marrow stromal mesenchymal cells in the treatment of acute myocardial infarction - Borsani, Paolo; Marazzi, Raffaella; Passi, Alberto; Mariscalco, Giovanni; Vigetti, Davide; Salerno-Uriarte, Jorge A.; Sala, Andrea (Archives of Medical Science, 2009)
Introduction: Aim of the study to investigate the efficacy of bone marrow stromal mesenchymal cells (BMSCs) in the early stages of acute myocardial infarction (AMI) in a rat model. Material and methods: Bone marrow was collected from lower limbs of male Wistar rats. Cells were prepared and cultured. Myocardial infarction was induced in female Wistar rats by coronary occlusion. After 30 min, rats received an intramyocardial injection of BMSCs (n = 9) or culture medium (control, n = 11). Echocardiography was performed at baseline and 30 days later, before heart excision. RT-PCR was performed and presence of chromosome Y, NKX2.5, troponin I, GATA4, VEGF-a, VEGF-R1, and KDR was investigated in lesion areas and in the posterior wall. Results: At day 30, a significant decrease in ejection fraction (LVEF) (46.6 ±16.2% vs. 35.6 ±16.0%, p = 0.035) and a marked increase in end-diastolic (LVEDd) (6.74 ±0.75 mm vs. 8.92 ±1.59 mm, p = 0.012) and end-systolic (LVESd) diameters (5.32 ±0.99 mm vs. 7.47 ±1.68 mm, p = 0.012) were evident in the control group. Bone marrow stromal mesenchymal cells-treated rats showed no difference in LVEF (36.8 ±12.1% vs. 44.8 ±12.3%, p = 0.262), LVEDd (7.92 ±0.89 mm vs. 7.76 ±1.34 mm, p = 0.671), or LVESd (6.65 ±1.15 mm vs. 6.21 ±1.42 mm, p = 0.624). Chromosome Y was detected only in lesion areas of BMSC-treated hearts. Expression of NKX2.5, troponin I, GATA4, VEGF-a, VEGF-R1, and KDR was significantly higher in lesion areas of treated hearts. Conclusions: Cell therapy with BMSCs seems effective in the early stages of AMI, preventing LVEF worsening and remodelling. Injected cells give origin to muscular and endothelial cells. It is necessary to clarify whether new cells directly derive from injected cells, or originate from resident or circulating cells by stimulation or chemotaxis.